2020
DOI: 10.36303/sagp.2020.1.4.0041
|View full text |Cite
|
Sign up to set email alerts
|

Sick and tired of COVID-19: long haulers and post viral (fatigue) syndromes

Abstract: COVID-19 patients may face a long and winding road to recovery. Outcomes of critically ill patients have been well described, including in China, Italy and the USA, and particularly in the comorbid elderly. However, short-, medium- and long-term health consequences are being realised not only in those that were hospitalised, but also in outpatients with milder or asymptomatic illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Numerous research groups reported widespread persisting symptoms in COVID-19 patients for up to 6 months after SARS-CoV-2 infection (70,75,(123)(124)(125)(126)(127)(128)(129)(130)(131)(132)(133)(134)(135)(136)(137)(138)(139)(140)(141)(142). They also described practice on the management of post-acute COVID-19 and performed comprehensive analyses of health-related quality of life (70,75,123).…”
Section: Widespread Persistent Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous research groups reported widespread persisting symptoms in COVID-19 patients for up to 6 months after SARS-CoV-2 infection (70,75,(123)(124)(125)(126)(127)(128)(129)(130)(131)(132)(133)(134)(135)(136)(137)(138)(139)(140)(141)(142). They also described practice on the management of post-acute COVID-19 and performed comprehensive analyses of health-related quality of life (70,75,123).…”
Section: Widespread Persistent Symptomsmentioning
confidence: 99%
“…They also described practice on the management of post-acute COVID-19 and performed comprehensive analyses of health-related quality of life (70,75,123). Furthermore, numerous editorials, reviews, news articles, clinical updates, narrative interviews, and focus groups have been published to explore what it is like to live with long-term COVID-19, also trying to emphasize the putative pathophysiology, risk factors, and treatments (124)(125)(126)(127)(128)(129)(130)(131)(132)(133)(134)(135)(136)(137)(138)(139)(140)(141)(142). Two cohort studies on severe/critical COVID-19 patients reported persistent physiological impairment and decrease in quality of life in more than half of the patients at up to 6 months of follow up (77,100).…”
Section: Widespread Persistent Symptomsmentioning
confidence: 99%
“…Patients with co-existing depression or anxiety also suffer from post-COVID fatigue longer than healthy individuals without psychiatric conditions [15,26]. As mentioned above, breathlessness or shortness of breath has been identified as a significant cause of fatigue [27] and is also related to the need for ICU admission and respiratory assistance, comorbid lung conditions, older age, and obesity [28].…”
Section: Fatiguementioning
confidence: 99%
“…There is currently no evidence assessing the potential direct associations between acute COVID-19 severity and fatigue after recovery from COVID-19 [24]. There is also a lack of research on inflammation markers, changes in cell counts, and pro-inflammatory agents with post-COVID-19 fatigue [28]. These are important research areas because central factors such as neurotransmitter levels, inflammation, and intrinsic neuronal excitability might contribute to COVID-19 fatigue [23].…”
Section: Fatiguementioning
confidence: 99%
“…Although in some cases COVID-19 patients were asymptomatic, many people complained from pneumonia, cough, fever, and gastrointestinal [GI] problems [ 2 , 3 ]. Recently, the long haul COVID-19 illness started to gain recognition whereby some patients suffer from symptoms in the long term even when their viral tests were confirmed negative [ 4 ].…”
Section: Introductionmentioning
confidence: 99%